4, 4, 8, 8‐Tetranitroadamantane‐2, 6‐diyl Dinitrate: A High‐Density Energetic Material. Issue 7 (22nd January 2015) - Ling, Yifei; Ren, Xiaoli; Lai, Weipeng; Luo, Jun
Abstract: The novel high‐performance energetic material 4, 4, 8, 8‐tetranitroadamantane‐2, 6‐diyl dinitrate has been synthesized and fully characterized. The synthetic strategy features the construction of the adamantane skeleton with different functional groups at adjacent methylene carbon atoms to overcome the problems associated with the ortho effect and steric crowding, and is amenable to the synthesis of other polynitroadamantanes. The experimentally determined physical properties as well as the calculated detonation properties indicate that this compound exhibits high thermal stability (220 °C), high density (1.852 g cm –3 ), and excellent detonation velocities (8529 m s –1 ) and pressures (33.43 GPa). Abstract : The novel high‐performance energetic material 4, 4, 8, 8‐tetranitroadamantane‐2, 6‐diyl dinitrate has been synthesized by the formylation of 1, 5‐cyclooctanedione followed by intramolecular aldol condensation to construct the adamantane skeleton.